Sarah's gift - Perry, Marta (New York, NY Berkley Books, 2011)
Amish midwife Sarah Mast moves to Pleasant Valley for a fresh start to run the birthing center her aging aunt can no longer manage. When a criminal complaint is filed against Sarah, she must find the strength to defend her practice and win the trust of the man and the community she has come to love.
Keywords: Amish women -- Fiction; Midwives -- Fiction; Amish -- Fiction; Amish Country (Pa.) -- Fiction; Christian fiction; Love stories